A Psycho-Spiritual Approach in Islamic Education: A Multisite Study of Spiritual and Psychic Potentials in Two Pesantren in North Sumatra - Wawan Arbeni; Muzakkir; Nurussakinah Daulay (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
The purpose of this study is to investigate the implementation of a psycho-spiritual approach in Islamic education at Pondok Pesantren Madani Ikhwanul Hasanah in Deli Serdang and the Modern Tahfidzul Qur’an Pesantren Raudhatul Mufassirin in South Labuhan Batu, North Sumatra. This study also seeks to examine the spiritual (rūḥānī) and psychic (nafsānī) potentials embedded within the educational practices of both institutions. Employing a qualitative methodology with a multisite design, this research utilizes case studies conducted at the two pesantren.. The findings reveal that: (1) the Qur’an conceptualizes spiritual and psychic potentials as foundational elements for shaping students’ character and behavior; (2) the psycho-spiritual educational principles identified across both pesantren include tawḥīd, tazkiyat al-nafs, self-awareness, mujāhadah, patience, gratitude, and iḥsān; (3) the implementation of psycho-spiritual education remains partial, with religious practices and study circles serving as the primary instructional mediums, thereby indicating the need for a more structured and integrated curriculum; and (4) the main challenges in applying psycho-spiritual education lie in educators’ limited practical understanding and the tendency to position spirituality as a supplementary activity rather than as the core foundation of the educational process. This study concludes that Qur’an-based psycho-spiritual education holds significant potential as a holistic educational model that harmonizes students’ cognitive, affective, and spiritual dimensions. The findings are expected to offer theoretical contributions to the development of Islamic educational frameworks and provide practical guidance for pesantren in designing integrative curricula that nurture students who are virtuous, faithful, and competitive.